Semiotics and Meaning in the Song “Cundamani” by Denny Caknan: Pierce's Approach - Wardani, Hana Tri; Ekawati, Mursia (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This research analyzes the lyrics of the song “Cundamani” by Denny Caknan using Peirce's semiotic approach, which involves the concepts of icon, index, and symbol. The purpose of this research is to reveal the deep meaning in the song lyrics through the identification and interpretation of linguistic signs. This song was chosen because it contains some lyrics that contain symbolic meanings that can be analyzed using Peirce's semiotic approach. The method used is a qualitative analysis of the song lyrics, where data is collected through translation and classification of icons, indices, and symbols. The results show that the meaning of the song “Cundamani” is built through the interaction between the signs. Icons in the lyrics, such as tears and light, represent real objects, while signifiers associate feelings with actions, and symbols refer to social concepts such as love and hope. The star symbol, for example, depicts guidance and support in the face of life's difficulties. In conclusion, this semiotic analysis reveals the emotional, spiritual and relational messages contained in the song, including the theme of love.